Antibiotic resistance patterns of group B streptococci in pregnant women. - Berkowitz, K (1990)
This study examined the antibiotic resistance patterns of group B streptococci (GBS) isolated from gravid women. A total of 156 vaginal and cervical isolates of GBS were examined for resistance to penicillin, ampicillin, clindamycin, cefoxitin, gentamicin, and erythromicin. No resistance to penicillin or ampicillin was found, nor was penicillinase production demonstrated. A high level of resistance to gentamicin was noted (91%). Of the isolates examined, 9, 9.5, and 15.3% exhibited either resistance or intermediate susceptibility to erythromycin, clindamycin, and cefoxitin, respectively. Thirty strains (19%) exhibited a multiple antibiotic resistance pattern. Given the high penicillin and ampicillin treatment failure rates when attempting to eradicate vaginal GBS colonization and our findings of higher and multiple drug resistance patterns of GBS, the selection of an alternative antibiotic regimen is of considerable clinical importance. We recommend that routine reporting of GBS susceptibilities by clinical laboratories be adopted.